Intracerebral Haemorrhage after Illicit Use of Sildenafil: A Case Report - Arti Shukla; Raghavendra Vagyannavar (International Journal of Medical Science and Clinical Research Studies, 2024)
Sildenafil(viagra) has become one of the top selling over the counter product for the treatment of male erectile dysfunction.(1) We report a case of 34year male patient admitted in our ICU with history of severe headache followed by sudden loss of consciousness after ingestion of two tablets of sildenafil(50mg) land up intracerebral bleed and died. There are many cases in the literature reporting intracerebral or subarachnoid haemorrhage associated with use of sildenafil while sexual contact.